Internalizing and externalizing symptoms in children during the COVID-19 pandemic: a systematic mixed studies review - Levante, Annalisa; Martis, Chiara; Bianco, Federica; Castelli, Ilaria; Petrocchi, Serena; Lecciso, Flavia (Frontiers in Psychology, 2023)
Considering the vulnerability of children during the COVID-19 pandemic, devoting attention to the wellbeing of this population is warranted. The current protocol-based systematic review aims at extracting the papers published during 2020-2022 focusing on the impact of the COVID-19 pandemic on children’s internalizing/externalizing symptoms and their contributing determinants. Method. PROSPERO: CRD42022385284. An electronic search was conducted in 5 databases and the PRISMA diagram was applied. Inclusion criteria were: papers published in English and in peer-reviewed journals; papers published between January 2020/October 2022 involving children aged 5-13 years; qualitative, quantitative, and mixed studies. The standardized Mixed Method Appraisal Tool protocol appraised the quality of reviewed studies. Results. 34 studies, reporting a total of 40.976 participants, were included. The main characteristics of the studies were tabulated. The results showed an increase of children’s internalizing/externalizing symptoms during the pandemic. Disengagement from play activities and excessive use of internet were the children’s determinants most associating to their internalizing/externalizing symptoms. Girls showed more internalizing symptoms while boys more externalizing symptoms compared to the counterpart. Distress was the strongest parental factor mediating children’ internalizing/externalizing symptoms. The quality of studies was appraised as low (n = 12), medium (n = 12) and high (n = 10). Conclusion. The results suggest that interventions should be designed for children and parents, and that gender differences should be considered in the design of such interventions. The reviewed research was cross-sectional in design, and therefore could not predict them long term patterns and outcomes for children’ internalising and externalising symptoms. Therefore, future studies should consider longitudinal designs to determine the long-term effect of the pandemic.